Pelakor Syar’i: Kekerasan Simbolik Terhadap Perempuan dalam Media Sosial - Yelly Elanda; Ardanareswari Ayu Pitaloka (Jurnal Wanita dan Keluarga, 2022)
This article will discuss the comments of netizens about the perpetrators who have made women victims of online gender-based violence (KBGO). The abundance of texts, images, memes, videos and news about perpetrators has made women a legitimate object to be blasphemed, scorned and bullied through social media. Using Michael Foucault's theory of discourse analysis can expose all forms of violence against women on social media, especially those with regard to issues of infidelity and pelakor. The method used by this research is critical discourse analysis where this method seeks to uncover discourses or myths about actors. The results of this study indicate that there has been symbolic violence against women who are referred to as syar'i actors through social media. The discourse or myth of actors syar'i has hegemonized netizens to commit KGBO acts with various forms of symbolic violence by intercepting gender and religion. Identity attacks, cyber bullying, suing women's abuse, and sexual harassment are a collection of violence experienced by women with the stigma of being sharia perpetrators on social media. Often times the KGBO is not recognized by the perpetrators and victims, and this public oppression can only be accepted without resistance.